Evidence-based decision making for prison health. (13th November 2019) - Tavoschi, L
Abstract: The presentation will provide an overview of the current evidence base on prison health interventions, gaps and challenges for conducting research in prison settings. Evidence based decision making is relevant for prison health, not only in terms of resources allocation, but also in relation to interventions and implementation approaches. Yet scientific literature covering prison health is generally quite limited. Lack of research activities in prison settings may be the results of several factors, partly deriving from structural challenges, and partly from specific features of the prison population. These include supplementary ethical implications, issues related to confidentiality and management of personal information and shortage of health care and other staff trained in conducting research. Low priority attributed to prison health in the sub-national, national or international research agenda may result in less opportunities for funding. Grey literature and programmatic data are regarded as an additional source of information; however accurate or reliable data are rare in Europe. While evidence is limited, there is a growing interest in prison health in Europe. A number of systematic reviews conducted in recent years shed some new light on key aspects of epidemiology and healthcare in prison. At European level various institutions and agencies and national institutions have been engaged in prison health and have produced a number of authoritative documents, including a few guidance documents.